Single and mixed dithiocarbamato metal(III) complexes (Co, Rh, and Ir): Crystal and molecular structure description and interplay - Shotonwa, Ibukun Oluwaseun; Oduwole, Adebayo Ponle; Agosu, Oluwapelumi Martin; Yusuf, Abosede Funke; Eze, Simeon Okechukwu (European Journal of Chemistry, 2024)
This review focuses on the crystal and molecular structures of single and mixed dithiocarbamate ligands of cobalt, rhodium, and iridium in the +3 oxidation state. The complexities of their chelating and bridging modes come into play through modification of the substituents on the carbamate nitrogen atoms of the ligands and additional coordination of secondary phosphino-containing ligands, culminating in various applications such as biological, analytical, medicine, and catalysis. Other considerations include the geometrical coordination environments around the metal centres and their comparison with isostructural congeners. The distortions around the metal centres and their subsequent effects on the symmetries of bonds in the primary and secondary coordination spheres are discussed. The trans-effects of secondary P-ligands and their effects on geometrical alignment and structural stability have become valuable yardsticks in analyzing structural modifications and stabilities.